2000
DOI: 10.1159/000056815
|View full text |Cite
|
Sign up to set email alerts
|

Cell lines from the same cervical carcinomabut with different radiosensitivities exhibit different cDNA microarray patterns of gene expression

Abstract: Combining chemotherapy with radiotherapy has improved the cure rate among patients with cancers of the cervix. Although one-half to two-thirds of the patients can be cured by radiation alone, such patients cannot be identified at present and must therefore suffer the burden of chemotherapy. Our long-range goal is to identify those cervical cancers that are radiosensitive and could be cured by radiotherapy alone. The advent of methods that permit the simultaneous analysis of expression patterns of thousands of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…cytochrome CYP1B1 showed the greatest overexpression in radioresistant cell lines (7). at low patient numbers, the results did not reveal a modified risk in former uranium miners in terms of CYP1A1 or CYP1B1 polymorphisms and smoking status.…”
Section: Discussionmentioning
confidence: 62%
“…cytochrome CYP1B1 showed the greatest overexpression in radioresistant cell lines (7). at low patient numbers, the results did not reveal a modified risk in former uranium miners in terms of CYP1A1 or CYP1B1 polymorphisms and smoking status.…”
Section: Discussionmentioning
confidence: 62%
“…The relationship between cytochrome c oxidase and chemo or radioresistance has been reported in various tumor cell lines (15)(16)(17)(18)(19). Comprehensive gene analysis on a microarray in cervical carcinoma cells (squamous cell carcinoma) showed that MT-CO1 was increased by a factor greater than two in RRCs compared with radiosensitive cells (15).…”
Section: Discussionmentioning
confidence: 97%
“…Comprehensive gene analysis on a microarray in cervical carcinoma cells (squamous cell carcinoma) showed that MT-CO1 was increased by a factor greater than two in RRCs compared with radiosensitive cells (15). Also, in human acute myelogenic leukemia cells, MT-CO3 was upregulated in chemoresistant cells compared with in chemosensitive cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…The success or Carbon Ion-Enhanced Genes in Oral Cancer failure of radiotherapy can be affected by the radiosensitivity of the tumor target and the limits imposed on treatment by the radiosensitivity of normal tissues. Recently, several studies using microarrays technique have successfully identified and classified a set of human genes that are radiosensitive to X-ray irradiation 1,8,10,12,18,32) . Modern curative radiotherapy requires higher doses to tumors and minimal irradiation to the surrounding normal tissues.…”
Section: Discussionmentioning
confidence: 99%